"Imagine ahead - plan backwards": melding critical infrastructure planning with strategic foresight. Issue 3 (2nd September 2019) - Ratcliffe, John
Abstract: This paper does not purport to be a scientific paper in the normally accepted academic sense, but is more of an essay cum commentary on how the strategic foresight process can be employed with advantage in the planning and development of mega infrastructure projects. The long-term time horizons of critical infrastructure planning and development demand a robust methodology to allow for risk, uncertainty and change. This is "Strategic Foresight". Drawing on the author's considerable experience, the paper seeks to provide a practical and applied description of how this can be achieved and, to this end, it details and critiques the six-stage process deployed by the Futures Academy (The Futures Academy is an applied research and strategic consultancy organisation that was established to provide a creative approach towards strategic planning by providing professional guidance to those concerned with making long-term planning and investment decisions. It was established in January 2003 and located in the Faculty of the Built Environment at the Dublin Institute of Technology, Ireland.) to describe the methodology's practical application. Because key stakeholder engagement is so fundamental to the process, it necessarily embodies concern with a prevailing public policy agenda that is preoccupied with the ramifications of climate change and its implications for sustainable development, although this is not discussed in any great detail.